A Cross-sectional Survey of Enteral Feeding Tube Placement and Gastric Residual Aspiration Practices: Need for an Evidence-Based Clinical Practice Guideline. (October 2021) - Perumbil Pathrose, Sheeja; Spence, Kaye; Taylor, Christine; Psalia, Kim; Schmied, Virginia; Dahlen, Hannah; Badawi, Nadia; Gregory, Katherine; Peters, Karen; Foster, Jann
Abstract : Background: Preterm infants routinely require enteral feeding via nasogastric or orogastric tubes as an alternative to oral feeding to meet their nutritional needs. Anecdotal evidence suggests variations in practice related to correct tube placement and assessment of feed intolerance. Purpose: To determine the current practices of enteral feeding tube placement confirmation and gastric residual (GR) aspiration of neonatal clinicians in Australia. Methods: A cross-sectional online survey comprising 24 questions was distributed to nursing and medical health professionals working in Australian neonatal care units through 2 e-mail listservs made available by professional organizations. Findings: The survey was completed by 129 clinicians. A single method was practiced by 50% of the clinicians in confirming tube placement, and most common practice was assessing the pH of GR aspirate. The majority of respondents (96%) reported that they relied on GR aspiration and clinical signs to determine feeding tolerance and subsequent decisions such as ceasing or decreasing feeds. However, the frequency of aspiration, the amount and color of aspirate considered to be normal/abnormal, and decisions on whether to replace gastric aspirate or whether aspiration should be performed during continuous tube feeding varied. Implication for practice: This study demonstrated considerable variability in clinical practice for enteral feeding tube placement confirmation and GR aspiration despite most respondents reporting using a unit-based clinical practice guideline. Our study findings highlight the need for not only developing evidence-based practice guidelines for safe and consistent clinical practice but also ensuring that these guidelines are followed by all clinicians. Implication for research: Further research is needed to establish evidence-based methods both for enteral feeding tube placement confirmation and for the assessment of feeding intolerance during tube feeding. In addition, the reasons why evidence-based methods are not followed must be investigated.